Tobacco Control Efforts in Indonesia - Organization, World Health (Indonesian Journal of Cancer, 2008)
Tobacco Control Efforts in IndonesiaÂ full text: http://www.scribd.com/doc/45152830/Tobacco-Control-Efforts-in-Indonesia